Interference coexistence between wireless meter reading system in 470～510 MHz band and adjacent systems - Ruichen XU; Ji FANG; Hao DU; Xiaobo WANG (Dianxin kexue)
Current RF specification restrains the wireless meter reading system (WMRS) working in 470～510 MHz band.It is incapable of meeting new communication speed and coverage requirements of power network.Under the premise of ensuring that prior used communication systems in adjacent band work without interference,how to modify the related RF specification to improve communication ability of WMRS is one of the problems to be solved at present.Firstly,the domestic frequency spectrum allocation in 450～566 MHz band was analyzed.Then,based on RF parameters of 3 kinds of WMRS from State Grid and deterministic computation and ray tracing simulation method,the interference coexistence between the WMRS and adjacent communication systems,which including broadcast television system,CDMA450 system,railway train dispatching system and FDD-LTE system was studied.At last,some suggestions for revision of relevant RF specifications were obtained.